CPR in correctional facilities: a missed opportunity? - Christopher Scott Sampson; Julie A. W. Stilley; Elizabeth Kendrick; Kayla Riel (BMC, 2022)
Abstract In the incarcerated population, the largest ethnic and racial group is Black people. Heart disease is known as the leading causes of death in the United States which can lead to cardiac arrest. Layperson cardiopulmonary resuscitation (CPR) has been shown to provide a benefit and increase likelihood of return of spontaneous circulation (ROSC). Recent research shows that in witnessed out of hospital cardiac arrests, the likelihood of receiving bystander CPR was found to be less among Black or Hispanic people when compared to White persons. One neglected area for layperson CPR training are these correctional facilities. This population is known to have higher rates of diabetes, high blood pressure and coronary artery disease, all of which contribute to an increased risk of acute coronary syndrome. A search was performed of the NEMSIS database. When comparing witnessed cardiac arrest, incidents without bystander interventions occurred more frequently than expected if the arrest was witnessed by a family member or other lay person. These interventions included bystander CPR or AED placement with or without defibrillation. The data presented shows that there is an unmet need of additional lay person CPR training in correctional facilities which could be implemented for little cost.